Plasmid- and chromosome-mediated dissimilation of naphthalene and salicylate in Pseudomonas putida PMD-1. - Zuniga, M C (1981)
Pseudomonas putida PMD-1 dissimilates naphthalene (Nah), salicylate (Sal), and benzoate (Ben) via catechol which is metabolized through the meta (or alpha-keto acid) pathway. The ability to utilize salicylate but not naphthalene was transferred from P. putida PMD-1 to several Pseudomonas species. Agarose gel electrophoresis of deoxyribonucleic acid (DNA) from PMD-1 and Sal+ exconjugants indicated that a plasmid (pMWD-1) of 110 megadaltons is correlated with the Sal+ phenotype; restriction enzyme analysis of DNA from Sal+ exconjugants indicated that plasmid pMWD-1 was transmitted intact. Enzyme analysis of Sal+ exconjugants demonstrated that the enzymes required to oxidize naphthalene to salicylate are absent, but salicylate hydroxylase and enzymes of the meta pathway are present. Thus, naphthalene conversion to salicylate requires chromosomal genes, whereas salicylate degradation is plasmid encoded. Comparison of restriction digests of plasmid pMWD-1 indicated that it differs considerably from the naphthalene and salicylate degradative plasmids previously described in P. putida.